Scanning the Landscape of Flux Compactifications: Vacuum Structure and Soft Supersymmetry Breaking - AbdusSalam, S; Conlon, J; Quevedo, F; Suruliz, K (2007)
We scan the landscape of flux compactifications for the Calabi-Yau manifold $\mathbb{P}^4_{[1,1,1,6,9]}$ with two K\" ahler moduli by varying the value of the flux superpotential $W_0$ over a large range of values. We do not include uplift terms. We find a rich phase structure of AdS and dS vacua. Starting with $W_0\sim 1$ we reproduce the exponentially large volume scenario, but as $W_0$ is reduced new classes of minima appear. One of them corresponds to the supersymmetric KKLT vacuum while the other is a new, deeper non-supersymmetric minimum. We study how the bare cosmological constant and the soft supersymmetry breaking parameters for matter on D7 branes depend on $W_0$, for these classes of minima. We discuss potential applications of our results.